Aliran Romantisme dalam Kesusastraan Arab - Dyah Adila Perdana; Tatik Mariyatut Tasnimah (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2022)
This article aims to discuss the Romanticism that developed rapidly in Arabic literature. This study used descriptive qualitative method. The research technique used is the listening and note-taking technique. The problems raised in this research are: 1) What is the History of Romanticism in Arabic Literature; 2) How was the influence of Romanticism in Arabic Literature; 3) Who are the figures of the Arab Romanticism and their works. The results obtained are 1) The history of Romanticism in Arabic literature was influenced by the west when Napoleon set foot on Arab lands and also as a critique of the Classical School. 2) The influence of Romanticism in Arabic Literature, namely the emergence of several literary groups associations and also the renewal of magazines and newspapers in the Arab world. 3) One of the figures of Arab Romanticism, namely Khalil Mutran, Khalil Gibran and Ahmad Zaki Abu Syadi